THE YORUK WOMAN - Mehmet AK (Fırat University, 2019)
The woman of the Yoruks keeping Turkish old family structure is both the backbone of the family and the arbiter among the family and in the management of the tent. The Yoruk woman has a crucial role in the transmission of the cultural backlog to the posterity. There are also Yoruk woman heroes took place in history since they have combative and independent habit because of the natural habitat they live in. The Yoruk women, mentioned about their various facilities in travellers’ observations, are active and effective in all areas of the social life. They use folk medicine. They treat the patients with plant derived mixtures prepared by themselves. The women undertake most of the workload in active life between yaylags (summer highland pastures) and winter quarters. The women, doing most tasks such as carrying migration waggons, also route and drive the herd on the migration routes. The Yoruk women, also hosting the quests, are quite skilful on cooking delicious meals from the animal products. The women do all kinds of works from the process of wool and goat hair spinning to producing last products in weaving which develops parallel to the animal husbandry. Their weaving products having